Percutaneous Foot Surgery - Chica Cusme, Jhonny (Revista Universidad de Guayaquil, 2009)
The foot is one of the most complex structures in the human body; it allows for the synchronized execution of walking, adapts to changes in surface, and to different demands required for our movement, from simple walking to running, jumping, or climbing stairs. This function is performed hundreds, if not thousands, of times a day, month after month, and year after year.The high demand of work to which our feet are subjected, genetic predisposition, overuse, and the little care they receive, generate countless injuries.